Catamenial Pneumothorax: Surgical Repair of the Diaphragm and Hormone Treatment - Leong, Annabelle C (The Royal College of Surgeons of England, 2006)
Catamenial pneumothorax is defined as spontaneous pneumothoraces occurring within 72 h before or after onset of menstruation. It is rare but clinical index of suspicion should be high in ovulating women with spontaneous pneumothoraces. The mechanism is unclear but is thought to involve pre-existing or acquired diaphragmatic defects and endometrial implants. Traditional therapy involving hormonal treatment or surgical pleurodesis alone is associated with high rates of recurrence. A series of four patients with catamenial pneumothorax managed at our institution is presented to highlight the condition to various surgical specialties to whom it may present, and to emphasise the importance of both surgical and hormonal interventions in preventing recurrence. Each patient underwent video-assisted thoracoscopic inspection of the diaphragm, mechanical pleurodesis and, most importantly, repair of diaphragmatic defects with an artificial mesh. Surgical treatment was strictly followed by a course of gonadotrophin-releasing hormone analogue therapy in three patients, with no recurrence to date (longest follow-up 45 months). The fourth patient suffered a postoperative recurrence when hormonal treatment was delayed for 6 weeks, stressing the importance of hormonal treatment in conjunction with surgery.